Association of food security and dietary diversity with stunting among toddlers in Gunungkidul regency, Indonesia - Rindi Nuryani; Paratmanitya, Yhona; Veriani Aprilia (Indonesian Nutrition Association, 2025)
Background: Stunting is impaired child growth due to prolonged undernutrition. In 2022, Indonesia’s stunting prevalence was 21.46% (SSGI), with Gunungkidul regency in Yogyakarta, Indonesia experiencing the highest rate at 23.5%. food security and dietary diversity can influence the occurrence of stunting in toddlers. Objective: This study aims to determine the association of food security and dietary diversity with stunting among toddlers in Gunungkidul Regency. Methods: This cross-sectional study was conducted in the Wonosari and Gedangsari District, Gunungkidul Regency. The sample of this study were 105 children from 6 Posyandu (integrated health care center), which were selected based on the stunting prevalence. The sample were selected using quota sampling techniques. Household food security was assessed using a questionnaire adapted from the 2012 USDA Household Food Security Survey Module, and dietary diversity was assessed using a questionnaire adapted from the 2011 Food and Agriculture Organization (FAO) guidelines. Data were analyzed using the Chi-Square test. Results: More than 30% of the children were stunted (31.4%), 51.5% had dietary diversity in the low and medium categories, and 44.8% of respondents come from food insecure families. There was a significant relationship between dietary diversity and stunting (p<0.05), however the relationship with food security was not statistically significant (p>0.05). Conclusion: Dietary diversity is significantly associated with stunting among toddler however food security is not related to stunting. Caregiver education promoting diverse toddler diets, especially local foods, is needed.